Predictive Elements of Obstructive Urolithiasis in Sheep* - Maciel, Thiago Arcoverde; de Oliveira, Clédson Calixto; Bastos Afonso, José Augusto; Maior Júnior, Rinaldo José de Souto; Fagliari, José Jurandir; Mathias, Luís Antônio; Oliveira, Daniela; Baraldi Artoni, Silvana Martinez; Amoroso, Lizandra (Acta Scientiae Veterinariae, 2019)
Background: Urolithiasis is an economically important disease that has considerable significance for sheep farming. With the tissue and biochemical changes resulting from the development of this disease, metabolic disorders and immune response are established. Hemogasometric evaluation allows the identification of systemic acid-base imbalances quickly. Acute phase proteins (AFP) have in the last two decades become the biomarkers of choice in human and veterinary medicine. To date, no biomarker studies have been published for sheep with obstructive urolithiasis. Thus, this study aimed to analyze the hemogasometric kinetics in obstructive urolithiasis in sheep and the AFP that can be used as early biomarkers in this disease. Materials, Methods & Results: In this study, 14 healthy male Santa Inês sheep, aged approximately 90 days, fed on calculogenic diet for 120 days. The animals were examined weekly, including observation of clinical signs, and blood and urine analysis were performed. For comparative analysis purposes, at the end of the experiment, sheep that developed obstructive urolithiasis were extracted from the initial experimental group D1 (without urolithiasis) and became part of the second experimental group D2 (with urolithiasis). In the pre-experimental period and on the day of slaughter, venous blood samples were harvested for hemogasometric tests, with a maximum time of 15 minutes between collection and analysis, to ensure the reliability of the results obtained. The pH, pCO2, pO2, EB, tCO2, HCO3-, stHCO3-, tHb, sO2 and Hct, Na+, K+ and Ca2+ ions were quantified. To identify and measure immunoglobulins (A and G) and AFP, samples from sheep that developed obstructive urolithiasis (D2) were analyzed. Blood samples were harvested weekly until the clinical manifestation of the disease, totaling 16 samples, when IgA, IgG, ceruloplasmin, transferrin, albumin, α1-antitrypsin, haptoglobin and α1-acid glycoprotein concentrations were measured. Elevation of pCO2 was observed between D1 and D2, but there was a significant difference (P < 0.05) only in the final moments (FMs). Although EB, tCO2, HCO3-, stHCO3- increased between moments in the same group and between groups at the same time, significant differences were recorded only in the FMs. Higher values were observed for Na+, K+ in the FMs. The AFP of sheep that developed the disease oscillated between moments, however, significant difference (P < 0.05) over time was observed only in haptoglobin and transferrin. Discussion: The disease occurred in five of the 14 animals studied, demonstrating the effectiveness of the formulated diet in inducing the disease. Through the analysis of blood gases, plasma bicarbonate concentration and excess base or deficit it was possible to diagnose disturbances in acid base balance, characterizing a picture of metabolic alkalosis in animals with urolithiasis. Mean pH was not significantly different between groups, but sheep that developed urolithiasis had alkalosis. Final values of tCO2 and HCO3- indicate the compensatory organic response, which, together with the analysis of the averages of HCO3- and EB, reflect the metabolic alkalosis picture. The AFP have different responsiveness among them. Haptoglobin and transferrin were the most reliable biomarkers among the studied AFP to predict obstructive urolithiasis, with transferrin showing atypical behavior, characteristic of positive AFP.